Healthcare in an unstable climate: the case for health climate change resilience - Paul J Cummins (Environmental Research: Health)
As a response to the well-documented projects for how anthropogenic climate change (ACC) will negatively impact human health, health and bioethics scholars have argued for the urgency of mitigating ecological damage healthcare systems cause. Mitigation is not the only focus because ACC is already affecting health. Under current plans to reduce emissions, the sixth Intergovernmental Panel on Climate Change (IPCC) predicts warming to exceed safe levels. Climate health scholars have begun to advocate for climate change adaptation (CCA) as it is essential to anticipate and prepare for how extreme ACC will affect health. CCA strategies that emphasize continuity of operation in the face of extreme weather events dominate. These plan project the future climate to be much like the present one, just worse, and assume an unwarranted future of climate stability. Recent scientific evidence indicate ACC is accelerating faster than climate models predicted. We may be moving from an era of climate stability to an era of instability. The dominance of CCA in preparing for ACC will, at best, preserve the status quo for population health at the expense of envisioning initiatives to help all people live healthier lives in a radically changed world. To prepare for an unstable climate future, healthcare should adopt a stance of climate change resilience that prioritizes public health initiatives to secure healthier lives among a broader population segment.